MARKETING POTENTIAL OF RTD (READY TO DRINK) TEA IN THE MIDST OF THE COVID-19 PANDEMIC - Daman Sudarman; Dwi Kartini; R. Arief Helmi; Rita Komala Dewi (PalArch's Journal of Archaeology of Egypt / Egyptology, 2022)
Competition in the packaged tea industry is very tight, thus requiring every business actor to have a strategy in order to attract consumers by fully understanding the purchasing decision process. The purpose of the study is to determine the Marketing Potential of RTD Tea (Ready to Drink) in the Midst of the Covid-19 Pandemic. A plethora studies have examined social media, marketing alliances and marketing innovations variables and their relationship to marketing potential, yet only few studies that examines them during the COVID-19 pandemic. Hence this research wants to shed a light on this situation. This research designed with a quantitative approach, based on the positivism paradigm. The main data source of this research is a company that produces ready-to-drink tea in the Greater Jakarta area (Jakarta, Bogor, Depok, Tangerang, Bekasi) which is a member of the Soft Drink Industry Association. While secondary data was obtained from various institutions such as the Indonesian Soft Drinks Association (ASRIM), the Association of Food and Beverage Entrepreneurs (GAPMMI) and data from various other sources. The population of this research are companies that produce and market ready-to-drink tea in the Greater Jakarta area (Jakarta, Bogor, Depok, Tangerang, Bekasi) which are members of the Soft Drink Industry Association. To analyze the influence between existing variables, this study will use Path Analysis. The findings reveal that social media, Marketing Alliance has a positive and significant effect on Marketing Potential, social media, Marketing Alliance has a positive and significant impact on Marketing Innovation.